Wild fauna as roadkill on a highway in the semiarid region of northeastern Brazil - de Lima Ferreira, Erly; Lima, Silvio; S. Souza, J. Weverton; Medeiros, Paulo Roberto (Ethnobiology and Conservation, 2023)
The death of wild vertebrates run over by motor vehicles on highways is one of the main causes of the loss of wildlife diversity. The aim of the present study was to investigate the diversity of wild fauna in roadkill incidents on a stretch of highway in the semiarid region of Brazil. The survey was conducted between March 2020 and May 2021 through active searches using a motorcycle. Killed vertebrates were analyzed and photographed in situ. Wild fauna was studied based on ecological descriptors, speed of movement and average rate of roadkill incidents. We compared total observed richness to that expected using nonparametric estimators. A total of 464 road-killed vertebrates were represented by two species of amphibians, 17 reptiles, 17 birds and 10 mammals. Amphibians were the most affected, totaling 245 individuals. Colubridae was the family with the largest number of species affected. Boiruna sertaneja and Boa constrictor were the only medium-size to large snakes killed. Herpailurus yagouaroundi and Leopardus tigrinus are respectively categorized as “least concern” and “vulnerable” according to the IUCN. The species accumulation curves continued to rise, showing no sign of approaching to an asymptote. Chao 2 and Jack 2 were the main estimators for road-killed wild vertebrates considering total richness. The diversity reported here is considered to be underestimated and greater monthly sampling efforts are required. Conservation strategies are urgently needed for the protection of wild vertebrate fauna to mitigate the staggering loss of biodiversity caused by the construction and operation of roads and highways in Brazil.